2011
DOI: 10.1029/2010jb007937
|View full text |Cite
|
Sign up to set email alerts
|

The apparent explosion moment: Inferences of volumetric moment due to source medium damage by underground nuclear explosions

Abstract: [1] Classical explosion source theory relates isotropic seismic moment to the steady state level of the reduced displacement potential. The theoretical isotropic moment for an incompressible source region M t is proportional to cavity volume V c created by pressurization of materials around the point of energy release. Source medium damage due to nonlinear deformations caused by the explosion will also induce volume change V d and radiate seismic waves as volumetric, double-couple, and compensated linear vecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 58 publications
3
37
0
1
Order By: Relevance
“…The functional form of the distance term comes from the power-law dependence discussed earlier, which becomes linear after the logarithmic transformation. The functional form of the HOB term is the hyperbolic tangent (tanh), a sigmoid function, which is similar to the one used to describe coupling as a function of DOB in Patton and Taylor (2011). The tanh function well describes the behavior for r s ≫ h s that is the case in this study.…”
Section: Seismic Data and Methodsmentioning
confidence: 96%
“…The functional form of the distance term comes from the power-law dependence discussed earlier, which becomes linear after the logarithmic transformation. The functional form of the HOB term is the hyperbolic tangent (tanh), a sigmoid function, which is similar to the one used to describe coupling as a function of DOB in Patton and Taylor (2011). The tanh function well describes the behavior for r s ≫ h s that is the case in this study.…”
Section: Seismic Data and Methodsmentioning
confidence: 96%
“…In this case, the generation of those wave occurs near the explosion source; probably due to oscillations of an asymmetrical shaped cavity. Patton & Taylor (2011) found that a non-isotropic radiation pattern for long-period waves might be a contribution from material damage in the source medium. Observed normal faulting mechanisms might be a consequence of slapdown of spalled layers.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of "changes of large-scale morphological features or surface changes such as displaced rocks or boulders" (Schlittenhardt et al, 2010) in mountainous terrain is a robust finding from which we infer that there was minimal free-surface damage for both 2006 and 2009 tests. On the other hand, most historic nuclear tests had significant nonlinear, free-surface interactions causing permanent deformations and a dilated source medium (Patton and Taylor, 2011). This late-time rock damage (Patton, 2012) radiates long-period Rayleigh waves through a Poisson effect involving vertical extension accompanied by lateral contraction.…”
Section: Re-evaluation Of Surface-wave Excitation By Dprk Testsmentioning
confidence: 99%
“…For this paper, we used the explosion Halfbeak (819 m, 365 kT; Springer et al, 2002). Its DOB is great enough to ensure full coupling, and the announced yield (W) is in a range in which the effects of damage on long-period Rayleigh waves are expected to be minimal due to recompaction of the source medium by spall slapdown (Patton and Taylor, 2011; see their fig. 3).…”
Section: Re-evaluation Of Surface-wave Excitation By Dprk Testsmentioning
confidence: 99%
See 1 more Smart Citation